O gênero Anredera (Basellaceae) no estado do Paraná, Brasil - Nunes, Maurício Gonçalves; Engel, Mathias Erich (Acta Biológica Paranaense, 2015)
<htm>O gênero Anredera (Basellaceae) no estado do Paraná, Brasil </htm>